Feedback has a positive effect on cognitive function during total sleep deprivation if there is sufficient time for it to be effectively processed. (January 2016) - Roach, Gregory D.; Lamond, Nicole; Dawson, Drew
Abstract: This study examined whether the provision of feedback and the interval between successive stimuli interact to affect performance on a serial simple reaction time test during sleep deprivation. Sixteen participants (9 female, 7 male, aged 18–27 yr) completed four versions of the 5-min psychomotor vigilance task for a handheld personal digital assistant (PalmPVT) every 2 h during 28 h of sustained wakefulness. The four versions differed in terms of whether or not they provided feedback immediately after each response, and whether the inter-stimulus intervals (ISIs) were long (2–10 s) or short (1–5 s). Cognitive function was assessed using reciprocal response time and percentage of responses that were lapses (i.e., had a response time ≥ 500 ms). Data were analysed using repeated measures ANOVA with three within-subjects factors: test session, feedback, and ISI. For both measures, the only significant interaction was between feedback and ISI. Cognitive function was enhanced by feedback when the ISIs were long because it provided motivation. Cognitive function was not affected by feedback when the ISIs were short because there was insufficient time to both attend to the feedback and prepare for the subsequent stimulus. Highlights: We examined performance on the psychomotor vigilance task—a serial simple reaction time test—during 28 h of sustained wake. The provision of feedback and the length of the inter-stimulus interval (ISI) interacted to affect performance. Feedback after each response resulted in better performance when the ISI ranged from 2–10 s. Feedback after each response did not affect performance when the ISI ranged from 1–5 s. When the ISI is long, it is possible that feedback provides motivation. When the ISI is short, it is likely that there is not time to both attend to feedback and prepare for the next stimulus.